2001
DOI: 10.1161/01.str.32.7.1539
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme Inhibition With Enalapril Slows Progressive Intima-Media Thickening of the Common Carotid Artery in Patients With Non–Insulin-Dependent Diabetes Mellitus

Abstract: Background and Purpose-Whether angiotensin-converting enzyme (ACE) inhibitors have any clinically significant antiatherogenic effects in humans remains unproven. We undertook a prospective randomized clinical trial of 98 patients with non-insulin-dependent diabetes mellitus (NIDDM) to examine the efficacy of ACE inhibition with enalapril for preventing intima-media (IM) thickening of the carotid wall as measured ultrasonographically. Methods-Ninety-eight NIDDM patients were randomly assigned either to enalapri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 49 publications
2
67
0
6
Order By: Relevance
“…A recent meta-analysis of 21 randomized clinical studies (6,317 patients) published before December 2011 found that statin therapy is associated with a favorable decrease in the CCA-IMT ( 0.029 mm, 95% CI: 0.045, 0.013) 93) . Other clinical trials using antihypertensive, antidiabetic or antithrombotic drugs have also evaluated the carotid IMT as a surrogate marker for subclinical atherosclerosis 15, 16,20,94) . A meta-analysis of eight randomized 2012 88) .…”
Section: Is the Carotid Imt Useful For Cvd Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis of 21 randomized clinical studies (6,317 patients) published before December 2011 found that statin therapy is associated with a favorable decrease in the CCA-IMT ( 0.029 mm, 95% CI: 0.045, 0.013) 93) . Other clinical trials using antihypertensive, antidiabetic or antithrombotic drugs have also evaluated the carotid IMT as a surrogate marker for subclinical atherosclerosis 15, 16,20,94) . A meta-analysis of eight randomized 2012 88) .…”
Section: Is the Carotid Imt Useful For Cvd Riskmentioning
confidence: 99%
“…Therefore, the 2010 American College of Cardiology Foundation/American Heart Association (ACCF/AHA) guidelines advocated the use of carotid IMT at a class IIa level for the assessment of cardiovascular risk in asymptomatic adults with an intermediate risk of CVD 11) . Multiple clinical trials using lipid-lowering, antihypertensive, and/or antidiabetic drugs have used the carotid IMT as a surrogate clinical endpoint [12][13][14][15][16][17][18][19][20] . However, a meta-analysis of 41 randomized trials showed that decreases in the carotid IMT do not predict a reduction in the cardiovascular events 21) .…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that treatment with dipeptidyl peptidase‐4 inhibitors seems to prevent the progression of carotid atherosclerosis regardless of disease burden. Previous studies showed that treatment with statins and angiotensin‐converting enzyme inhibitors reduces the progression of carotid atherosclerosis in patients with type 2 diabetes mellitus3, 4. In this subgroup analysis, sitagliptin still attenuated the progression of carotid IMT, even in patients who were receiving those therapies.…”
mentioning
confidence: 51%
“…In addition, Ang II can also directly activate NAD(P)H by inducing translocation of GTPase rac1 protein to the cell membrane, 19 or by phosphorylating and translocating p47phox to cell membrane. 20 Activation of NAPDH oxidase provides superoxide that reacts with eNOS-derived NO and leads to eNOS uncoupling in hypertension. 21 In addition, xanthine oxidase expression and activity are also increased by Ang II in a NADPH oxidase-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…22 Thus ACEI may decrease the oxidative stress in part by limiting Ang II induced superoxide production by NAD(P)H oxidase and reduce the downstream effects of superoxide. 20 ACEI therapy may also down regulate activation of redox-sensitive proinflammatory signals and limit lipid peroxidation and peroxynitrite generation. This study brings new evidence in humans that supports the hypothesis that ACEI increase antioxidant activity and decrease lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%